STUDI COLLABORATIVE GOVERNANCE PROGRAM CITARUM HARUM DALAM PERBAIKAN KUALITAS AIR SUNGAI CITARUM - Agung Prayoga; Khaerul Umam; Sakrim Miharja (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2022)
In an effort to improve the water quality of the Citarum River, the central government launched a program called the Citarum Harum Program through Presidential Regulation (Perpres) no. 15 of 2018, this program is targeted to be completed for a period of 7 years from the beginning of the issuance of the policy. The purpose of this research is to find out in depth how the implementation of Collaborative Governance carried out by the Sector 6 Task Force team of the Citarum Harum Program where the program can provide good results in improving the water quality of the Citarum River. Descriptive method through qualitative approach is the method used in this research, observation, interview, and documentation study are the three techniques used in the data collection process in this study. The results of the study indicate that the collaboration process carried out by the Citarum Harum Sector 6 Task Force team in general has gone well, causing the water quality of the Citarum River to show a better graph. It is based on 5 dimensions written by Ansell and Gash. Where the five aspects include; face-to-face dialogue; build trust; commitment to the process; mutual understanding; and intermediate results. But on the other hand, there is still a need for improvement from some of these aspects to provide even more maximum results and the problems that exist in the Citarum River can gradually be resolved.